Fear of Happiness Scale and Fragility of Happiness Scale: Evidence of Their Psychometric Adequacy in Polish - Edyta Janus (Rehabilitacja Medyczna)
Introduction: This is the first study in which psychometric properties regarding the Polish version of the Fear of Happiness Scale (FHS) and The Fragility of Happiness Scale (FOHS) are investigated.Aim: The aim of the study was to translate as well as assess the reliability and validity of the FHS and FOHS.Material and methods: The study participants comprised 351 adults who consented to participation. Non-random sampling was applied. The inclusion criteria were age and employment status. The respondents filled in the FHS and FOHS questionnaires and provided basic sociodemographic data.Results: Using Cronbach’s α, FHS and FOHS demonstrated high internal consistency, α = .85 and α = 0.80, respectively. Due to all items having good discriminatory power, there were no grounds for removing any of the items.Conclusions: The proposed Polish versions of the FHS and FOHS can be used to assess fear of happiness and beliefs concerning its fragility, and they are viable in studies related to various scientific disciplines. These scales can also be useful for the science of physical culture, especially within the context of examining beliefs that may affect the quality of human life and health. The cognitive aspect is very important for the success of rehabilitation. Beliefs have consequences in human actions.